Effect Of Government’s Policy to Build 1 Million Houses on Performance of Housing and Apartment Credits of Banks Listed in Indonesia Stock Exchange during Period 2015-2017 - Purnamasari, Laely (Jurnal Ilmiah Ilmu Administrasi Publik, 2021)
Through the Directorate General of Housing Financing, the Ministry of Public Works and Public Housing estimates that by 2025 the number of housing needs in Indonesia will reach 30 million units based on calculating housing needs (backlog) of population growth. In 2015, the Government Program's number of achievements for the Construction of One Million Houses was around 700 thousand units. In 2016, it reached 805,169 housing units, and in 2017 onwards, it is expected to reach the target of 1 million houses per year. The main problem in a housing development or the property sector is land availability and various communities' purchasing power. The government policy related to the construction of 1 million houses coupled with easy licensing of the land sector and provision of subsidies such as the liquid housing finance facility (FLPP) has stimulated the banking sector and other financial institutions to finance the property sector. The residential segment, namely apartments and housing, is the most significant contributor to the national property capitalization value, reaching 55.8%. The growth rate of the capitalization value of the residential sector reached 16.5%, from Rp. 152.7 trillion to Rp. 177.9 trillion in 2017. Focusing on KPR and KPA during the 2015-2017 period at banks listed on the Stock Exchange Indonesia.